ORGANIZATION OF POWER SUPPLY OF THE FIRST CATEGORY RECEIVERS FOR PERSPECTIVE CIVIL AVIATION AIRCRAFT - A. V. Kechin (Naučnyj Vestnik MGTU GA, 2018)
The article deals with the issue of providing electric power to the first category receivers in the emergency mode of the power supply systems operation of perspective and modernized aircraft. The analysis of the published scientific works performed both in Russia and abroad, and aimed at solving problems of analyzing abnormal operations mode, synthesizing power supply systems and controlling them in order to prevent dangerous consequences is carried out. The authors considered the ingenious technical solutions aimed at providing the necessary quality power supply for the first category receivers in the emergency operation modes of the aircraft power supply systems for the safe completion of flight and landing. The research analysis and generalization of data on the technical characteristics of units and devices developed by the world's leading manufacturers of aviation equipment and used as emergency sources of electrical power on board modern civil aviation aircraft has been completed. The advantages and disadvantages of each technical solution are determined, as well as limitations to the area of their application are formed. The analysis of perspective emergency sources of the electric power including those, which previously were not applied in aviation because of their insufficient technical perfection, for example, hydrogen electrochemical generators is carried out. Based on the performed analysis, a solution which allows improving the operating modes of the electrical batteries is proposed. The offered solution makes it possible to increase the reliability and durability of electrical batteries, as well as the power supply duration of the first category receivers from them.